Analisis Pengaruh Islamicity Performance Index Terhadap Profitabilitas Bank Umum Syariah di Indonesia Tahun 2014-2018 - Nabilla, Siva; Pahlevi, Rizal (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2021)
This study aims to determine the effect of the Islamicity Performance Index on the Profitabilityof Islamic Commercial Banks in Indonesia in 2014-2018. Research variables consist of Return OnAsset (ROA), Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), and Islamic Income Ratiovs Non-Islamic Income Ratio (IsIR). The population of this research is all Islamic commercial banksin Indonesia. This research uses the purposive sampling method. The sample used in this study were9 Islamic Commercial Banks that meet the required criteria. The analysis method used is multipleregression. The results of this study indicate that according to the T-test (partially) the results are thePSR variable has a positive effect, the ZPR variable has a positive effect and the IsIR variable hasno and insignificant effect on the Return On Asset (ROA) of Islamic Commercial Banks. So it can beconcluded from the three variables tested, the PSR variable and the ZPR variable are variables thathave a positive effect in this study. Meanwhile, according to the F test (simultaneously), the results arethe variable Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), and Islamic Income Ratio vsNon-Islamic Income Ratio (IsIR) have a joint effect on Return On Assets (ROA). ) Sharia CommercialBank.